Pashtunwali in Jamil Ahmad’s The Wandering Falcon: an Exploration of Cultural Traditions and Narrative Dynamics - Saad Salman; Syed Hanif Rasool; Ahmed Jalal, (Dialogue Social Science Review (DSSR), 2025)
Pashtunwali is generally regarded as the Pashtun code of conduct practiced in the Pashtun region for centuries. Whereas Pashto literature invariably and Urdu literature occasionally refer to the aforementioned code of conduct, Pakistani fiction in English rarely brings images of such representation. Employing the codes of Pashtunwali explicated in the Pashto folkloric tradition, this paper aims to offer realistic depiction and exploration of Pashtunwali in Jamil Ahmad’s The Wandering Falcon. By delving into specific instances and character interactions, this paper aims to illuminate the cultural nuances and narrative dynamics influenced by Pashtunwali and provide a comprehensive understanding of the manifestation of Pashtunwali in The Wandering Falcon. This research paper seeks further to explore and dissect the manifestations of Pashtunwali within the novel, examining how cultural traditions impact character development, plot progression, and overall thematic elements.